KRITIK WACANA “ALLAH PERLU DIBELA” : TINJAUAN ULANG ATAS QS. MUHAMMAD AYAT 7 DAN Q. AL-HAJJ AYAT 40 - Royyani, Izza; Kumalasari, Aziza (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
AbstractThis article tries to review the understanding of Qs. Al-Hajj verses 40 and QS. Muhammad verse 7. From the verse quotation literally, Allah will reward those who help Him, concerning helping Allah Is this illustrated here as a favor to ordinary people? When should God need help? So it is necessary to emphasize the phrase